A Registry Based Approach to Suicide Research: Opportunities and Limitations in the Norwegian Population Representative Registries - Stene-Larsen, Kim; Hauge, Lars; Øien-Ødegaard, Carine; Reneflot, Anne (Santé mentale au Québec)

(untitled) (Revue Santé mentale au Québec, 2018)
Together with the other Nordic countries, Norway stands in a unique position internationally with its large population representative registries. By means of unique personal identification numbers assigned to all Norwegian citizens, as well as to immigrants who stay for more than 6 months, it is possible to construct individual record linkages covering an increasing number of years across different national registries. The Norwegian registries include, among others, information from the primary and specialist health care services, the prescription of drugs, and causes of death. In addition, they include sociodemographic information like year of birth, gender, immigration status, educational attainment, marital status, and the use of various social benefits. Norway is one of very few countries that have a nationwide registry on primary health care use. This registry gives the opportunity to explore the role of the primary health care services prior to suicide and in the follow-up of the suicide bereaved, which has been pointed out as one of the most promising areas for future suicide prevention. Linkages of Norwegian registries opens up new approaches in analyses and the possibility to explore a range of novel research themes, such as treatment trajectories and patterns of health care use prior to suicide and among the suicide bereaved.In this paper, we give a description of the Norwegian population representative registries applicable for suicide research. We discuss the analytic opportunities as well as the challenges and obstacles of a registry based research approach to suicide.The main strength of registry-based research on suicide is the ability to maintain data on the total population, the possibility to study small sub-populations or low-prevalent events, virtually continuous timelines in longitudinal data, few or no non-response or other missing data, no sample attrition, and the possibility of gaining access to large amounts of various health and sociodemographic information. In addition registry-based research allows investigation of hard-to-reach populations, such as groups of individuals with severe mental disorders or immigrants that traditionally have been difficult to recruit for participation in research projects.The opportunities presented in the article could motivate to do similar research in Canada and even inspire for cooperation between Norwegian and Canadian researchers on registry based research on suicide. In our opinion, registry-based research on suicide will play an increasingly important role in suicide research in the years to come.